Structural Analysis and Reinforcement Design of Sidewalk and Slab Elements in Composite Steel Bridges Based on SNI 1725:2016 and SAP2000 Simulation for Sustainable and Climate-Resilient Infrastructure - Setiawan, Randy; Diva, Priska Aura; Viktorgus; Hillary, Janne (WISE Pendidikan Indonesia, 2025)
This research explores both the structural behavior and environmental relevance of sidewalk and deck slab components in composite steel-concrete bridge systems, emphasizing principles of sustainability and resilience to climate change. The focus was placed on the structural planning of the Palempay 5 Bridge, a Class A bridge located in West Kalimantan, Indonesia, which features reinforced concrete for both pedestrian pathways and vehicle lanes. The design follows key Indonesian standards, including SNI 1725:2016 for bridge loading, SNI T-12-2004 for concrete bridge structures, and SNI 2847:2013 for general concrete design. Using SAP2000, the bridge components were analyzed under multiple loading scenarios such as dead loads, live loads, pedestrian impact, and environmental factors like wind and thermal variation. The reinforcement was designed to maximize efficiency while ensuring structural integrity and durability. The analysis demonstrated that a sidewalk thickness of 50 cm and a deck slab thickness of 20 cm, reinforced with D16 and D13 bars, provided sufficient strength and serviceability. Furthermore, the bridge elements were shown to perform effectively under environmental stresses, aligning with climate-resilient design principles. This study contributes to the development of environmentally conscious infrastructure by combining optimized structural design with ecological considerations. It offers practical insight for civil engineers seeking to implement designs that reduce material consumption, lower carbon emissions, and enhance durability in the face of environmental change.